Systematics of Malaysian woolly bats (Vespertilionidae: Kerivoula) inferred from mitochondrial, nuclear, karyotypic, and morphological data - Khan, Faisal Ali Anwarali; Solari, Sergio; Swier, Vicki J; Larsen, Peter A; Abdullah, M.T; Baker, Robert J (The Oxford University Press, 2010)
Examining species boundaries using data from multiple independent sources is an appropriate and robust method to identify genetically isolated evolutionary units. We used 5 data sets—cytochrome b (Cytb), cytochrome c oxidase (COI), amplified fragment length polymorphisms (AFLPs), karyotypes, and morphology—to estimate phylogenetic relationships and species limits within woolly bats, genus Kerivoula, from Southeast Asia. We genetically analyzed 54 specimens of Kerivoula from Malaysia, assigned to 6 of the 10 species currently reported from the country. Phylogenetic analyses of nuclear AFLPs (33 specimens) and mitochondrial DNA sequences from Cytb (51 specimens) and COI (48 specimens) resulted in similar statistically supported species-level clades with minimal change in branching order. Using comparisons of cranial and dental morphology and original species descriptions, we assigned the resulting phylogenetic clades to K hardwickii, K. intermedia, K. lenis, K. minuta, K. papillosa, K pellucida, and 1 unidentified species. Karyotypes further documented variability among the 6 clades. Five different karyotypes were identified, with 2 species having indistinguishable karyotypes. We compared our COI gene sequence data to 110 specimens of Kerivoula from Southeast Asia made available by researchers of the Barcode of Life Database. Our Cytb and AFLP species identifications were congruent with those in the COI database. Intraspecific geographic variation of about 5–7% sequence divergence was observed in Cytb and COI genes within both K. hardwickii and K. minuta. Relaxed molecular clock analyses indicated a late Oligocene to early Miocene origin of the Kerivoulinae with intraspecific diversification events coinciding with the late Pliocene and Pleistocene epochs in at least 6 species. Specimens from Sabah (northeastern Borneo) showed relatively high genetic divergence compared to those between Peninsular Malaysia and Sarawak (southwestern Borneo), indicating Pleistocene or Pliocene refugia in Borneo. We conclude that at least 1 distinct lineage of Kerivoula is yet to be described from Borneo and that the intraspecific geographic variation in some species agrees with previous studies on the diversification of flora and fauna in Borneo. Key words